Differential Regulation of Bcl‐xL Gene Expression by Corticosterone, Progesterone, and Retinoic Acid. Issue 6 (25th February 2016) - Morrissy, Steve J; Sun, Haipeng; Zhang, Jack; Strom, Joshua; Chen, Qin M.
ABSTRACT: Corticosterone (CT), progesterone (PG), and retinoic acid (RA) are capable of inhibiting Doxorubicin (Dox) from inducing apoptosis in rat cardiomyocytes. Mechanistically, CT, PG, and RA induce increases of Bcl‐xL protein and mRNA, and activate a 3.2 kb bcl‐x gene promoter. CT and RA, but not PG, induced the activity of a 0.9 kb bcl‐x promoter, containing sequences for AP‐1 and NF‐kB binding. RA, but not CT or PG, induced NF‐kB activation. CT, but not PG or RA, induced AP‐1 activation, and induction of the 0.9 kb bcl‐x reporter by CT was inhibited by dominant negative c‐Jun TAM‐67 or removal of AP‐1 binding site. Therefore, although CT, PG, and RA all induce Bcl‐xL mRNA and protein, three independent mechanisms are in operation: while CT induces Bcl‐xL via AP‐1 transcription factor, and RA induces NF‐kB activation and bcl‐x promoter activity, PG induces Bcl‐xL via a mechanism independent of NF‐kB or AP‐1.